PENGGUNAAN INSTAGRAM @premature.indonesia SEBAGAI MEDIA PROMOSI KESEHATAN DAN PENCEGAHAN PREMATURITAS - Rani Sukma Ayu Suteja; Umar Umar; Nimas Safira Widhiasti Wibowo; Dimas Ramadhiansyah (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
The number of premature births in Indonesia is still high and is often the cause of growth disorders and death in children. Due to a lack of public understanding of the health concerns associated with premature delivery, health promotion initiatives in this area are critical. Premature Indonesia (a non-governmental organization) exists to reach out to the wider public and create public awareness about the health risks associated with preterm births through both online and offline promotions. In response to technological advancements, the @premature.indonesia Instagram account, which focuses on education and information, was created. This study uses in-depth interviews as primary data and employs a qualitative technique and descriptive research type. Content analysis, literature review, and observation were used to gather secondary data. The findings show that Instagram helps the organization in efficiently presenting promotions through informative, interesting, and persuasive messages. They maximize the use of features like story, live, direct messages, captions, and hashtag insights. According to the results of content analysis classification on @premature.indonesia Instagram posts, the community has met primary categories.